Improved Performance of SiDREB2-SNAP Marker in Foxtail Millet by Optimum Primer Concentration, PCR Cycle, and DNA Polymerase Specificity - Wospakrik, Andrean Heskiel; Rizqullah, Ramadaniarto; Pahlevi, M Reza; Yudiansyah, Yudiansyah; Purwoko, Bambang Sapta; Suwarno, Willy Bayuardi; ARDIE, Sintho Wahyuning (Department of Agronomy and Horticulture, IPB University, 2026)
Foxtail millet (Setaria italica L. Beauv.) is an emerging carbohydrate-producing crop. It is considered a climate-resilient crop due to its tolerance to abiotic stresses. Breeding for abiotic-tolerant crops requires powerful tools such as molecular markers. The single-nucleotide amplified polymorphism (SNAP) marker, developed from a single-nucleotide DNA variation at a specific location in the plant genome, is a simple yet powerful PCR-based marker widely used in phenotype-related selection. A SiDREB2-based SNAP marker was previously developed based on a base variation at the 558th base pair (an A/G transition) in the SiDREB2 gene and used to estimate the drought tolerance in foxtail millet. However, the specificity of the marker depends on technical aspects, including the type of DNA polymerase used, primer concentration, and the number of PCR cycles. Here, we reported that non-specific and false positive amplicons can be eliminated by utilizing DNA polymerase with no 3’ to 5’ proofreading activity and reducing the final primer concentration to 1.25 μM. PCR cycle number 25 yielded the optimum specificity, while increasing the cycle to 30 resulted in false positive results. Altogether, our results showed that technical optimization is necessary for improving the specificity of the SNAP marker.